PERANCANGAN BUKU POP-UP PEMBUATAN KERIS DI PADEPOKAN BROJOBUWONO KARANGANYAR DENGAN TEKNIK V-FOLDING SEBAGAI MEDIA PENGENALAN KEPADA ANAK-ANAK - Arisandi, Rendi; Riyanto, Darwin Yuwono; Hidayat, Wahyu (Jurnal Art Nouveau, 2017)
The book is a print media that plays a role to provide educational information to all circles of society, pop-up books are books that contain an interactive element when opened and as if there was an object or object that emerged from within a pop-up book that provides  visualization  which  are  interesting. Indonesia has many cultural heritages, one of them is keris. But many do not know about the process of making keris, but behind the process of making kris and kris itself there are values  of life. This  is based on the results of interviews conducted on mpu kris making, teachers of art and culture experts history. The lack of knowledge on keris causes the low appreciation of the community, especially the children in Solo about the kris and its manufacturing process. Departing from the problem, this research   is intended to design the book Pop-Up keris making In Padepokan Brojobuwono Karanganyar with V- Folding technique as a medium of introduction to the children. Kata Kunci: Buku Pop-Up, Warisan Budaya Indonesia, Proses Pembuatan Keris